Love in Different Dimensions: Narrative and Dramaturgic Specificity of Brief Encounters by Kira Muratova - Tsibets, Ilya (Media - Culture - Social Communication, 2021)
The author aimed to present the possibilities of multidimensional analysis of the film text based on the example of Brief Encounters (1967) directed by Soviet and Ukrainian director Kira Muratova (1934–2018). The analysed film is an example of innovative thinking about film narration in Soviet cinema. The starting pointof the authorʼs deliberations is an introduction of the historical context in which the film was produced and outlining the framework situations which generate narrative schemes and imply meanings. Muratovaʼs full-length debut is an unconventional experiment with melodramatic film narration which, after returning from the screen nonentity in 1987 along with other “rehabilitated” films, has contributed to the emergence of a new type of reflection on censorship in Soviet cinema and its artistic shape.